Kontribusi Orientalis terhadap Studi Hadis Kontemporer Di Indonesia: Teori, Respons dan Sikap Sarjana Hadis - Ade Pahrudin (Refleksi: Jurnal Kajian Agama dan Filsafat, 2023)
This article aims to determine the contribution of orientalists to contemporary hadith studies in Indonesia, map developing theories, identify the responses and attitudes of Indonesian hadith scholars towards these theories through e-articles written in religious journals indexed in the Moraref portal of the Ministry of Religion. This research is library research. The method used in this research is content analysis. Data The main literature of this paper is e-articles in religious journals related to orientalism in contemporary hadith studies in Indonesia. The results of this research show the contribution of theories formulated by orientalists to the dynamics of contemporary hadith studies in Indonesia. The role of orientalists as skeptical outsiders creates a different perspective from Muslim hadith scholars, so that they build new theories in contemporary hadith studies. Orientalist theories that are discussed in contemporary hadith studies in Indonesia include; hadith fabrication theory, sunnah-hadith terminology, Common link, argumentum e-silentio, projecting back and isnad cum matan. The responses of hadith scholars to Orientalist theories is divided into several attitudes; descriptive-elaborative, descriptive-comparative, descriptive-appreciative and descriptive-critical.